Rate maximization and hyperbolic discounting in human experiential intertemporal decision making. (16th November 2017) - Seinstra, Maayke Suzanne; Sellitto, Manuela; Kalenscher, Tobias
Abstract : We experimentally show that during decisions between smaller-sooner and larger-later monetary rewards, devaluing future rewards meets and serves evolutionary principles of long-term reward rate maximization in human participants. The present data thus reconcile the economically flavored theory implying that choices are based on the incremental devaluation of reward as the time of its receipt passes, and the account rooted in behavioral ecology that predicts that choices should maximize reward rate in the long run. Abstract: Decisions between differently timed outcomes are a well-studied topic in as diverse academic disciplines as economics, psychology, and behavioral ecology. Humans and other animals have been shown to make these intertemporal choices by hyperbolically devaluing rewards as a function of their delays ("delay discounting"), thus often deemed to behave myopically. In behavioral ecology, however, intertemporal choices are assumed to meet optimization principles, that is, the maximization of energy or reward rate. Thus far, it is unclear how different approaches assuming these 2 currencies, reward devaluation and reward rate maximization, could be reconciled. Here, we investigated the degree at which humans ( N = 81) discount reward value and maximize reward rate when making intertemporal decisions. We found that both hyperbolic discounting and rate maximization well approximated the choices made in a range of different intertemporal choice design conditions. Notably, rate maximization rules provided even better fits to the choice data than hyperbolic discounting models in all conditions. Interestingly, in contrast to previous findings, rate maximization was universally observed in all choice frames, and not confined to foraging settings. Moreover, rate maximization correlated with the degree of hyperbolic discounting in all conditions. This finding is in line with the possibility that evolution has favored hyperbolic discounting because it subserves reward rate maximization by allowing for flexible adjustment of preference for smaller, sooner or larger, later rewards. Thus, rate maximization may be a universal principle that has shaped intertemporal decision making in general and across a wide range of choice problems.